Beyond Quantitative Easing Towards a New Monetary Theory - Obregón, Carlos (Journal of Management Policy and Practice, 2025)
In his article Interest and Prices, originally published in 1898, Wicksell summarized the two goals of monetary policy that today constitute the cornerstones of monetary theory. The first goal is to prevent monetary shocks due to excessive/or insufficient credit in the system, resulting in a conservative view of monetary policy. The second goal is to adequate the level of credit to changes in the real sector of the economy as reflected in changes in the real level of savings or investment. The first goal has been the main emphasis of the Quantitative Theory of Money which supports both Monetarism and Rational Expectations. The second goal was the route taken by Keynes who emphasized the volatility of investment as a main cause of economic instability. This article provides a third route that benefits from the two routes previously mentioned and proposes a new monetary theory.